2016
DOI: 10.4238/gmr.15017117
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of quercetin on acute myocardial infarction in rats

Abstract: ABSTRACT. To investigate the protective mechanism of quercetin on acute myocardial infarction (AMI) rats, an AMI rat model was established by ligating the left coronary anterior descending branch. The rats were randomly divided into the model group and low-and high-dose quercetin groups. The control group comprised sham-operated rats. The rats in the low-and high-dose quercetin groups were administered 100 and 400 mg/ kg quercetin, respectively, by gavage. The rats in the control and model groups were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…The decrease of the atherosclerotic lesions was not associated with the improvement of the lipid profile, but with the decreased inflammatory stress, measured as decreased IL-1 receptor, IKK and STAT3 [169,174]. In the rat model of acute myocardial infarction, quercetin administration determined the reduction of TNF-α, IL-1β expression in the myocardial tissue, in parallel with an increase of the antioxidant SOD and catalase activities [175]. Recently, a few clinical studies regarding the anti-inflammatory effects of quercetin in human subjects were published, but the results are controversial.…”
Section: Flavonolsmentioning
confidence: 87%
“…The decrease of the atherosclerotic lesions was not associated with the improvement of the lipid profile, but with the decreased inflammatory stress, measured as decreased IL-1 receptor, IKK and STAT3 [169,174]. In the rat model of acute myocardial infarction, quercetin administration determined the reduction of TNF-α, IL-1β expression in the myocardial tissue, in parallel with an increase of the antioxidant SOD and catalase activities [175]. Recently, a few clinical studies regarding the anti-inflammatory effects of quercetin in human subjects were published, but the results are controversial.…”
Section: Flavonolsmentioning
confidence: 87%
“…As such, the pharmacological implications of the effects of the methylated metabolites of Qu with respect to the antiplatelet effects of aspirin are worthy of consideration. Apart from these actions, one more recent study showed that Qu processes an antiapoptotic effect in ischemic myocardial damage [108]. Altogether, these studies demonstrated that Qu may be a promising drug for the treatment and prevention of atherosclerosis in ASCVD.…”
Section: Elimination Of Etiology Reduction Of Complications and Effmentioning
confidence: 91%
“…A recent study showed that oxidative stress is an important factor involved in the development of AMI. Quercetin significantly decreases MDA content, increases SOD and CAT activity, and regulates anti-inflammatory and anti-apoptosis processes to effectively protect against myocardium injury [87]. In addition, quercetin protects the heart from secondary cardiac dysfunction due to oxidative stress and inflammation.…”
Section: Application Of Antioxidant Activity In the Medicinal Fieldmentioning
confidence: 99%